2022
DOI: 10.2147/iprp.s354717
|View full text |Cite
|
Sign up to set email alerts
|

Sudanese Medical Doctors’ Perceptions, Expectations, Experiences and Perceived Barriers Towards the Roles of Clinical Pharmacists: A Cross-Sectional Study

Abstract: Purpose Interprofessional collaboration between physicians and clinical pharmacists has been shown to improve patients’ outcome by reduce medical errors, costs and patient adherence. Thus, the purpose of this study was to investigate the medical doctors’ perceptions, expectations, experiences, and perceived barriers regarding clinical pharmacists in Wad Medani. Methods A cross-sectional study was conducted at five major hospitals in Wad Medani, between April and June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The majority of Sudanese physicians who discussed their experiences with clinical pharmacists agreed that these experts are a reliable source of knowledge on both general and clinical drugs, and they frequently notify physicians of any clinical concerns with the prescriptions they write. 18 In our study, almost all of the interventions were accepted by physicians in consistence with the two studies in Taif and Jeddah, Saudi Arabia, which revealed that, (98.5%) and (97%) of clinical pharmacist interventions were accepted respectively. 8 , 19 The findings of this study were greater than the acceptance rate in Qatar at Alkhor Hospital (87.2%), 16 India (94.8%) 5 and in United Arab Emirates (94.7%.).…”
Section: Discussionsupporting
confidence: 68%
“…The majority of Sudanese physicians who discussed their experiences with clinical pharmacists agreed that these experts are a reliable source of knowledge on both general and clinical drugs, and they frequently notify physicians of any clinical concerns with the prescriptions they write. 18 In our study, almost all of the interventions were accepted by physicians in consistence with the two studies in Taif and Jeddah, Saudi Arabia, which revealed that, (98.5%) and (97%) of clinical pharmacist interventions were accepted respectively. 8 , 19 The findings of this study were greater than the acceptance rate in Qatar at Alkhor Hospital (87.2%), 16 India (94.8%) 5 and in United Arab Emirates (94.7%.).…”
Section: Discussionsupporting
confidence: 68%
“…This finding is consistent with the findings of several earlier investigations. 14,15,18 In addition, physicians in this study indicated that clinical pharmacists may enhance overall health outcomes and patient quality of life. These views are in agreement with those expressed earlier by Saudis and US doctors, who pointed out that clinical pharmacists' participation and recommendations increased the quality of patient care.…”
Section: Attitudes Aspectmentioning
confidence: 76%
“…In 2011, Hodeidah University became the first university to offer a clinical pharmacy program, and in 2013, it established the first independent college of clinical pharmacy. 9,10 Previous research has indicated that there are some variations in how doctors see various types of CPSs [11][12][13][14][15][16][17][18][19][20][21] and that doctors seem to have an improved perception of CPSs if they interact with pharmacists more often. 11,[15][16][17][18][19] Doctors in Sweden are skeptical of the expertise and understanding of clinical pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with limited collaboration reported in a previous Sudanese study where nearly half of the physicians either had never or rarely interacted with a C. Ph. [12] . Other reports have attributed physicians' discomfort with C. Ph.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mahmoud et al, physicians interacted with C. Ph. mainly to enquire about drug availability, alternatives, dosage, and drug interactions [12] . However, other studies concluded that practicing physicians in Egypt do not consider clinical pharmacists as a part of the healthcare team [11] .…”
Section: Introductionmentioning
confidence: 99%